The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1111/jam.14983
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Bacillus megaterium strain A14 alleviates cadmium accumulation in peanut: effects and underlying mechanisms

Abstract: Aims: A cadmium (Cd)-tolerant Bacillus megaterium strain A14 was used to investigate the effects and mechanisms of bacterial inoculation on peanut growth, Cd accumulation in grains and Cd fixation in Cd-contaminated soil. Methods and Results: Spectroscopic analysis showed that A14 has many functional groups (-OH, -NH2 and -COO et al.) distributed on its surface. The pot experiment indicated that compared to the Cd-contaminated soil alone treatment, inoculation with strain A14 increased shoot and root biomass b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Beneficial plant micro‐organisms are recommended as biological control agents (BCAs) in agricultural production due to their safety and environmental friendliness (Li et al, 2014; Mahapatra et al, 2022). At present, the use of beneficial micro‐organisms to improve crop health, and alleviate and protect plants from stress has become a research priority (Sahoo et al, 2013; Yao et al, 2021). Mohammad et al (2016) found that the endophytic bacterium Bacillus oryzicola YC7007 and its culture filtrate can significantly reduce rice bakanae by activating the JA‐hormone pathway and inducing systemic resistance against bakanae pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial plant micro‐organisms are recommended as biological control agents (BCAs) in agricultural production due to their safety and environmental friendliness (Li et al, 2014; Mahapatra et al, 2022). At present, the use of beneficial micro‐organisms to improve crop health, and alleviate and protect plants from stress has become a research priority (Sahoo et al, 2013; Yao et al, 2021). Mohammad et al (2016) found that the endophytic bacterium Bacillus oryzicola YC7007 and its culture filtrate can significantly reduce rice bakanae by activating the JA‐hormone pathway and inducing systemic resistance against bakanae pathogens.…”
Section: Introductionmentioning
confidence: 99%